Distribution of dissolved 137Cs, 131I and 238Pu at Eastern Mediterranean Sea in case of hypothetical accident at the Akkuyu Nuclear Power Plant. (October 2022) - Tsabaris, C.; Eleftheriou, G.; Tsiaras, K.; Triantafyllou, G.
Abstract: A coupled hydrodynamic/lagrangian particle drift model was applied to obtain the distribution of key radionuclides that are dispersed at the surface water (upper 100 m) of Eastern Mediterranean Sea, in case of an accident of Nuclear Power Plant at Akkuyu. The model was applied to simulate the dispersion of key artificial radionuclide concentration, in case of a hypothetical accident to assess issues related to sea health and potential hazards. The released radionuclide was found to have a favorable westward direction, following the prevailing currents. The variability of the predicted pattern is interpreted according to the near surface circulation patterns in the study area. The dispersion of key radionuclides ( 137 Cs, 238 Pu and 131 I) was studied in a spatial and temporal manner at the neighboring coasts of the location of the NPP. Furthermore, the fate of the plume was predicted for each month after the accident date close to the areas of Akkuyu, namely Cyprus, Rhodes Island, North Cretan coast, Cyclades and Syrian Coast. The annual study revealed that the radioactive plume is present with high concentration (maximum values of 1200 Bq m −3 for the long lived isotopes and 600 Bq m −3 for 131 I) in the location of the plant for short period of time (1–2 months), while the other areas are affected during the whole year with low level of activity concentration (20–50 Bqm −3 ). The ERICA Assessment Tool was also used to evaluate dose rates to common marine biota at the studied areas. Highlights: Hydrodynamic model application for studying the dispersion of radioactive plume at the East Mediterranean Sea. The prediction of the spatial dispersion of radioactive plume after 4 months of the accident date. Annual simulation of 137 Cs, 238 Pu and 131 I activity concentrations in selected areas close to the Akkuyu Nuclear Power Plant. Dose rates assessment to common marine biota in selected areas.